(untitled) (Ustozlar uchun, 2026)
This article examines the process of finding and evaluating Computer-Assisted Language Learning (CALL) resources as an essential component of modern language education. It discusses the importance of selecting appropriate digital tools, criteria for evaluating their effectiveness, and their role in enhancing language learning. Special attention is given to the types of CALL resources, their practical applications, benefits, and challenges. The study also provides strategies for effective use of CALL resources in both academic and professional contexts.